Is the Subsequent Kidney Transplantation Connected with Poorer Graft Function?. (July 2018) - Jędrzejko, Kalina; Kieszek, Rafał; Kwapisz, Magdalena; Durlik, Magdalena; Kwiatkowski, Artur
Abstract : 25% patients on the waiting lists are patients with renal allograft failure. In spite of the development of immunosupressive therapy, chronic rejection of renal graft remains a problem. The growing number of patients with failed kidney transplant are returning to dialysis program or are retransplanted. 406 kidney recipients that received a kidney graft between 2013 – 2015 in a single centre were taken to analysis. Analysis resulted in 33 pairs of patients: for one recipient in the pair it was the first transplantation (group 1) and for the other – the second or subsequent (group 2). Graft and patient survival, graft function, delayed graft function episodes, primary non-function and acute rejection episodes were taken to analysis in order to assess the outcome of kidney retransplantation. Follow-up period was 2 years. Delayed graft function was observed in both groups (p=0.3303). Despite in the second group there were twice as many episodes of acute rejection than in the first group (8 to 4), the results are not statistically significant (p=0.1420). Primary graft dysfunction was observed only in the second group. There were 5 patients that had lost their kidney graft during follow-up period in the second group. The probability of graft loss in the second group equalled as follow: 3% at the day of the transplantation, 12% after 3 months, 15% after 13 months. All of the patients survived two-years follow-up period. Similar eGFR was observed in time in both groups. There are no statistical differences of kidney graft function between patients with the first transplantation and those with the repeat one. The good results of kidney transplantation are attainable in both groups. It seems that retransplantation is the best treatment option for patients with primary graft failure.